PENDETEKSIAN MANIPULASI LAPORAN KEUANGAN MENGGUNAKAN BENEISH M-SCORE PADA PERUSAHAAN KONSTRUKSI BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2023 - Muhammad Rafi Naufal Fawwaz (CV. Adiba Aisha Amira, 2026)
This study aims to detect the potential of fraudulent financial statements in state-owned construction companies listed on the Indonesia Stock Exchange during the 2021–2023 period using the Beneish M-Score method. This research employed a quantitative method with a descriptive approach. The data used in this study were secondary data obtained from the companies’ financial statements and annual reports. The research sample consisted of PT Waskita Beton Precast Tbk, PT Wijaya Karya (Persero) Tbk, PT PP (Persero) Tbk, and PT Adhi Karya (Persero) Tbk selected using purposive sampling. The analysis was conducted by calculating the Beneish M-Score through eight financial ratios, namely DSRI, GMI, AQI, SGI, DEPI, SGAI, LVGI, and TATA. The results indicate that several state-owned construction companies were suspected of having the potential to manipulate financial statements. PT Waskita Beton Precast Tbk was indicated in 2022 and 2023, PT Wijaya Karya (Persero) Tbk in 2021 and 2022, PT PP (Persero) Tbk in 2022 and 2023, and PT Adhi Karya (Persero) Tbk in 2021 and 2023. The findings suggest that state-owned construction companies have a relatively high risk of fraudulent financial statements due to financial pressure, project complexity, and high leverage. Therefore, the Beneish M-Score method can be used as an early detection tool to identify potential financial statement manipulation in state-owned construction companies.